The effect of 8 or 5 years of denosumab treatment in postmenopausal women with osteoporosis: results from the FREEDOM Extension study. Issue 12 (December 2015) - Papapoulos, S.; Lippuner, K.; Roux, C.; Lin, C.; Kendler, D.; Lewiecki, E.; Brandi, M.; Czerwiński, E.; Franek, E.; Lakatos, P.; Mautalen, C.; Minisola, S.; et al.
Abstract Summary The FREEDOM study and its Extension provide long-term information about the effects of denosumab for the treatment of postmenopausal osteoporosis. Treatment for up to 8 years was associated with persistent reduction of bone turnover, continued increases in bone mineral density, low fracture incidence, and a favorable benefit/risk profile. Introduction This study aims to report the results through year 5 of the FREEDOM Extension study, representing up to 8 years of continued denosumab treatment in postmenopausal women with osteoporosis. Methods Women who completed the 3-year FREEDOM study were eligible to enter the 7-year open-label FREEDOM Extension in which all participants are scheduled to receive denosumab, since placebo assignment was discontinued for ethical reasons. A total of 4550 women enrolled in the Extension (2343 long-term; 2207 cross-over). In this analysis, women in the long-term and cross-over groups received denosumab for up to 8 and 5 years, respectively. Results Throughout the Extension, sustained reduction of bone turnover markers (BTMs) was observed in both groups. In the long-term group, mean bone mineral density (BMD) continued to increase significantly at each time point measured, for cumulative 8-year gains of 18.4 and 8.3 % at the lumbar spine and total hip, respectively. In the cross-over group, mean BMD increased significantly from the Extension baseline for 5-year cumulative gains of 13.1 and 6.2 % at the lumbar spine and total hip, respectively. The yearly incidence of new vertebral and nonvertebral fractures remained low in both groups. The incidence of adverse and serious adverse events did not increase over time. Through Extension year 5, eight events of osteonecrosis of the jaw and two events of atypical femoral fracture were confirmed. Conclusions Denosumab treatment for up to 8 years was associated with persistent reductions of BTMs, continued BMD gains, low fracture incidence, and a consistent safety profile.